Comparison of virtual reality rehabilitation and conventional rehabilitation in Parkinson's disease: a randomised controlled trial. (March 2020) - Pazzaglia, C.; Imbimbo, I.; Tranchita, E.; Minganti, C.; Ricciardi, D.; Lo Monaco, R.; Parisi, A.; Padua, L.
Abstract: Objective: To compare a 6-week virtual reality (VR) rehabilitation programme with a conventional rehabilitation programme in patients with Parkinson's disease. Design: Prospective, single-blinded, randomised controlled trial. Setting: Outpatients. Participants: Fifty-one patients with Parkinson's disease were assigned at random to a VR rehabilitation programme or a conventional rehabilitation programme. Interventions: Both programmes ran for 6 consecutive weeks, with a 40-minute session three times per week. Main outcome measures: The Balance Berg Scale (BBS) was used to measure balance. Secondary outcome measures were: Dynamic Gait Index (DGI) to evaluate ability to adapt gait to complex walking tasks; Disabilities of the Arm, Shoulder and Hand (DASH) scale to measure performance of the upper limb; and Short Form 36 (SF-36) to evaluate quality of life. Results: The VR rehabilitation programme led to an increase in BBS score 45.6 [standard deviation (SD) 7.9] vs 49.2 (SD 8.1), mean difference 3.6, 95% confidence interval (CI) 1.3 to 5.9; P = 0.003, DGI score [18.7 (SD 4.7) vs 20.2 (SD 4.2), mean difference 1.6, 95% CI 0.6 to 2.5; P = 0.003] and SF-36 mental composite score [37.7 (SD 11.4) vs 43.5 (SD 9.2), mean difference 5.8, 95% CI 0.4 to 11.3; P = 0.037], and a decrease in DASH scale score [29.6 (SD 17.5) vs 21.6 (SD 15.1), mean difference −7.9, 95% CI −13.7 to −2.2; P = 0.009]. In contrast, the conventional rehabilitation programme only led to a decrease in DASH scale score [30.3 (SD 18.1) vs 25.1 (SD 15.8), mean difference −5.2, 95% CI −8.8 to −1.5; P = 0.007]. Conclusion: These findings suggest that rehabilitation is useful in Parkinson's disease, and the VR rehabilitation programme was more effective in determining overall improvement than the conventional rehabilitation programme. Clinical trial registration number: : NCT02807740.